Students’ innovativeness and higher education for sustainable development: A bibliometric approach - Li, Xiang; Pu, Ruihui (Humanities and Social Sciences Letters, 2023)
Innovativeness plays a decisive role in the progress of society, the sustainable development of nations, and the success of individuals in the era of information technology and knowledge economy, especially because the world is now confronted with major challenges such as climate change, environmental degradation, social inequality and resource exhaustion that have no ready solutions. As cradles for talent, higher education institutions attach great importance to promoting the innovative capabilities of their students. This study aims to introduce the existing studies on students’ innovativeness in institutions of higher learning for sustainable development. This study applies a bibliometric analysis by conducting collaboration, co-citation, co-reference, and co-occurrence analysis on university students’ innovativeness toward sustainable development. A total of 1,531 academic publications have been collected from the Web of Science Core Collection database from 2011 to 2021 and further analyzed. The major researchers and publications, productive countries or regions, collaborative institutions, research hotspots, and trends related to the innovativeness of college students are identified in this study. By adopting Co-occurrence (COOC) and VOSviewer to analyze and visualize the data, this research reveals that college students’ innovation capability continues to be an emerging research issue. Training, entrepreneurship education, and entrepreneurial intention are identified as the gaps for further studies. The results of this study suggest that academia in higher education institutions and government agencies are strongly encouraged to enhance the innovativeness of college students to tackle the unsustainable issues haunting society today.